NILAI-NILAI KETAUHIDAN: TELAAH STARTEGI PEMBELAJARAN BAHASA ARAB BERBASIS ILMU TAUHID - Salamuddin Salamuddin; Siti Nur Holizah Hasibuan (Reflektika, 2023)
A common problem that occurs in education is the failure to achieve educational goals. The problem also occurs in Arabic language learning caused by the lack of utilization and lack of improvisation of strategies in the learning carried out. The existing strategy seems menoton and results in a lack of student interest in Arabic.  For this reason, there is a need for strategies in learning to increase the learning drive so that it can improve cognitive and intellectual abilities. The aspect of monotheism is belief in god without associating it. This principle became the main purpose of the teachings under the Prophet Muhammad SAW. This study aims to find out methods and strategies in Tawhid-based Arabic language learning. The results of the research conducted show that there is a need for a special strategy in instilling the value of tawhid through Arabic language learning. This is an effort to provide an understanding that everything in this world is related to Allah SWT, including in the field of education. And so that students can have good morals and civility in everyday life because they always feel watched by God the creator.